O banalności śmierci. Azyl dla uchodźców we współczesnej sztuce - Sulikowska-Dejena, Agata (Wydział Sztuki UR, 2017)
The aim of the article is to present the work of artists who are focused on the plight of refugees and who have made that humanitarian crisis the main theme of their projects. Their artistic intervention is characterized by a profound social involvement and a desire to build an alternative narration – sensitive to suffering, putting man in the first place and emphasizing the fact that first of all we constitute a community of humans. Contemporary art has become a symbolic shelter for the refugees and a place allowing them to regain their lost dignity. Using various media and artistic strategies, like: site-specific activities, installations, artistic interventions, graffiti, participatory art, the authors show that a dialogue is possible, that despite the fears it is possible to build a community above prejudices, whose members do not differ so much from each other. Artists confirm with practical actions that we always deal with a sensitive, suffering person, and the pain evoked by the death of the loved ones is equally excruciating on both sides of the fence. The discussed works can be analyzed in terms of aesthetic values but in order to fully understand their meaning we have to consider the content, the message to the audience, which the authors have included in the form. That is why the article attempts to show the works and the words of the artists in a broader, social and philosophical perspective.
The banality of death. A shelter for refugees in contem porary art
Keywords: sztuka współczesna; schronienie; uchodźcy; artystyczna interwencja; zaangażowanie społeczne; dialog; contemporary art; shelter; refugees; artistic intervention; social involvement; dialogue